Cerebrospinal fluid neurogranin/β‐site APP‐cleaving enzyme 1 predicts cognitive decline in preclinical Alzheimer's disease. Issue 1 (9th November 2018) - Kirsebom, Bjørn‐Eivind; Nordengen, Kaja; Selnes, Per; Waterloo, Knut; Torsetnes, Silje Bøen; Gísladóttir, Berglind; Brix, Britta; Vanmechelen, Eugeen; Bråthen, Geir; Hessen, Erik; Aarsland, Dag; Fladby, Tormod
Abstract: Introduction: The cerebrospinal fluid neurogranin (Ng)/β‐site amyloid precursor protein‐cleaving enzyme 1 (BACE1) ratio may reflect synaptic affection resulting from reduced beta‐amyloid (Aβ) clearance. We hypothesize that increased Ng/BACE1 ratio predicts the earliest cognitive decline in Alzheimer's disease. Methods: We compared Ng/BACE1 levels between cases with subjective cognitive decline (n = 18) and mild cognitive impairment (n = 20) both with amyloid plaques and healthy controls ( APOE ‐ε4+, n = 16; APOE ‐ε4‐, n = 20). We performed regression analyses between cerebrospinal fluid levels, baseline hippocampal and amygdala volumes, and pertinent cognitive measures (memory, attention, Mini Mental State Examination [MMSE]) at baseline and after 2 years. Results: Ng/BACE1 levels were elevated in both subjective cognitive decline and mild cognitive impairment compared to healthy controls. Higher Ng/BACE1 ratio was associated with lower hippocampal and amygdala volumes; lower baseline memory functions, attention, and MMSE; and significant decline in MMSE and memory function at 2‐year follow‐up. Discussion: High Ng/BACE1 ratio predicts cognitive decline also in preclinical cases with amyloid plaques. Highlights: CSF Ng/BACE1 may confer synapse loss tied to β‐amyloid disease mechanism. CSF Ng/BACE1 is increased already in preclinical cases with amyloid plaques High CSF Ng/BACE1 is the only biomarker related to lower baseline memory function. High CSF Ng is the only biomarker related to reduced baseline hippocampal volume. High CSF Ng predicts decline in verbal memory function at 2‐year follow‐up.